Enhanced field emission properties From plasma treated Ti3C2Tx (MXene) emitters. (25th November 2020) - Hong, X D; Zheng, H R; Liang, D
Abstract: MXenes are an emerging family of 2D transition metal carbides and nitrides and have already shown potential in various applications. However, up to now, studies on the field emission application of MXenes are scarce. In this study, the field emitters based on the Ti3 C2 Tx (MXene) flakes were prepared by facile solution process and the effect of different plasmas (H2, Ar, O2 ) on the field emission properties of Ti3 C2 Tx films was investigated. The plasma treated Ti3 C2 Tx films showed significantly better field emission properties than that of as-deposited Ti3 C2 Tx films. Compared to the Ar and O2 plasma treated Ti3 C2 Tx films, the H2 plasma treated Ti3 C2 Tx films displayed lower turn-on field (8.5 V/ μ m) and larger maximum current density (1222 μ A cm −2 ). The H2 plasma treated Ti3 C2 Tx films also showed good emission stability. These results suggested the potential of the H2 plasma treated Ti3 C2 Tx films as electron source of vacuum electronic devices.